ARH Family of ADP-Ribose-Acceptor Hydrolases - Hiroko Ishiwata-Endo; Jiro Kato; Sachiko Yamashita; Chanbora Chea; Kazushige Koike; Duck-Yeon Lee; Joel Moss (Cells, 2022)
The ARH family of ADP-ribose-acceptor hydrolases consists of three 39-kDa members (ARH1-3), with similarities in amino acid sequence. ARH1 was identified based on its ability to cleave ADP-ribosyl-arginine synthesized by cholera toxin. Mammalian ADP-ribosyltransferases (ARTCs) mimicked the toxin reaction, with ARTC1 catalyzing the synthesis of ADP-ribosyl-arginine. ADP-ribosylation of arginine was stereospecific, with β-NAD+ as substrate and, α-anomeric ADP-ribose-arginine the reaction product. ARH1 hydrolyzed α-ADP-ribose-arginine, in addition to α-NAD+ and O-acetyl-ADP-ribose. Thus, ADP-ribose attached to oxygen-containing or nitrogen-containing functional groups was a substrate. Arh1 heterozygous and knockout (KO) mice developed tumors. Arh1-KO mice showed decreased cardiac contractility and developed myocardial fibrosis. In addition to Arh1-KO mice showed increased ADP-ribosylation of tripartite motif-containing protein 72 (TRIM72), a membrane-repair protein. ARH3 cleaved ADP-ribose from ends of the poly(ADP-ribose) (PAR) chain and released the terminal ADP-ribose attached to (serine)protein. ARH3 also hydrolyzed α-NAD+ and O-acetyl-ADP-ribose. Incubation of Arh3-KO cells with H2O2 resulted in activation of poly-ADP-ribose polymerase (PARP)-1, followed by increased nuclear PAR, increased cytoplasmic PAR, leading to release of Apoptosis Inducing Factor (AIF) from mitochondria. AIF, following nuclear translocation, stimulated endonucleases, resulting in cell death by Parthanatos. Human ARH3-deficiency is autosomal recessive, rare, and characterized by neurodegeneration and early death. Arh3-KO mice developed increased brain infarction following ischemia-reperfusion injury, which was reduced by PARP inhibitors. Similarly, PARP inhibitors improved survival of Arh3-KO cells treated with H2O2. ARH2 protein did not show activity in the in vitro assays described above for ARH1 and ARH3. ARH2 has a restricted tissue distribution, with primary involvement of cardiac and skeletal muscle. Overall, the ARH family has unique functions in biological processes and different enzymatic activities.